Financial Feasibility Analysis of Capture Fisheries as a Basis for Socio-Economic Policy for Fishermen in West Tegal District, Tegal City, Central Java - Asnawi Asnawi; O.D. Soebhakti Hasan; Sobariah Sobariah; Irman Nur Hamzah (Program Studi Sosial Ekonomi Perikanan, Fakultas Ilmu Kelautan dan Perikanan, Universitas Hasanuddin, 2026)
Small-scale capture fisheries play an important role in supporting the livelihoods and economies of coastal communities; however, their sustainability is strongly influenced by business feasibility and appropriate policy support. This study aims to analyze the financial feasibility of capture fisheries as a basis for formulating socio-economic policies for fishers in West Tegal District, Tegal City. The study employed purposive sampling involving 65 fishers as respondents. Primary data were collected through interviews with fishers, while secondary data were obtained from relevant government institutions. The analysis used a socio-economic approach based on business and investment feasibility indicators, including the Revenue-Cost (R/C) Ratio, Break-Even Point (BEP), Payback Period (PP), Return on Investment (ROI), Net Present Value (NPV), and Internal Rate of Return (IRR). The results indicate that capture fisheries businesses in the study area are economically feasible, as demonstrated by an R/C Ratio of 3.8, an ROI of 36%, an NPV of IDR 570.37 million, and an IRR of 37.44%. These findings indicate that the sustainability of fishers' livelihoods is determined not only by technical production aspects but also by appropriate financing policies and effective management of fishing assets. Therefore, the findings provide a basis for formulating policies that support small-scale fishers through improved access to financing, fishing fleet renewal, and strengthened fisher capacity and institutional arrangements at the local level, as a foundation for socio-economic policies for small-scale capture fisheries.